Smart choices - Hammond, John S.
In Smart Choices, John Hammond, Ralph Keeney, and Howard Raiffa—experts with over 100 years of experience resolving complex decision problems—offer a proven, straightforward, and flexible roadmap for making better and more impactful decisions, and offer the tools to achieve your goals in every aspect of your life